Short‐term storage of salmonids semen in a sodium alginate‐based extender. (10th August 2016) - Merino, O.; Figueroa, E.; Cheuquemán, C.; Valdebenito, I.; Isachenko, V.; Isachenko, E.; Sánchez, R.; Farías, J.; Risopatrón, J.
Summary: Short‐term storage of semen is a useful strategy for preservation of fish spermatozoa. However, there is a significantly decrease on sperm function mainly due to oxidative stress. In this way, sodium alginate plays an important role as free radical scavenger compound. Accordingly, the aim of our study was to analyse the effect of a sodium alginate‐based extender on sperm function in the short‐term storage of salmonids semen. Samples of Salmo salar, Oncorhynchus kisutch, and Oncorhynchus mykiss were stored in Storfish ® (Ext‐C) and Storfish ® supplemented with sodium alginate (Ext‐A) during 10 days at 4°C. After storage, motility, viability, mitochondrial membrane potential (ΔΨmit), superoxide anion (O2 − ) level and DNA fragmentation (DNA Frag) were assessed. Ext‐A had positive effect in preservation of sperm motility, viability, ΔΨmit, O2 − level and DNA integrity in the three species analysed compared to control samples. In Ext‐A, the spermatozoa of S. salar and O. mykiss showed significantly higher motility, viability and ΔΨmit than O. kisutch . However, O. kisutch and O. mykiss had significantly lower O2 − level than S. salar, and DNA fragmentation in O. kisutch and S. salar was significantly lower than in samples of O. mykiss ( p < 0.05). Dilution of salmonids semen in a sodium alginate‐based extender is effective for protecting sperm quality during 10 days of short‐term storage.